The Effect of Oil Contaminated on Collapse Pattern in Gypseous Soil Using Particle Image Velocimetry and Simulation - Hala Mahmood Jawad; Zuhair Kadhim Jahanger (Civil Engineering Journal, 2024)
Gypseous soil covers approximately 30% of Iraqi lands and is widely used in geotechnical and construction engineering as it is. The demand for residential complexes has increased, so one of the significant challenges in studying gypsum soil due to its unique behavior is understanding its interaction with foundations, such as strip and square footing. This is because there is a lack of experiments that provide total displacement diagrams or failure envelopes, which are well-considered for non-problematic soil. The aim is to address a comprehensive understanding of the micromechanical properties of dry, saturated, and treated gypseous sandy soils and to analyze the interaction of strip base with this type of soil using particle image velocimetry (PIV) measurement and Plaxis 3D simulation. The results showed that high-resolution digital cameras captured soil deformation using PIV, displacement fields, and velocity vectors were generated, which helped identify different sand movement zones. Further, PIV showed punching and general shear failure in uncontaminated and soaked contaminated gypsum soils, respectively. Moreover, the Plaxis results corresponded well with the PIV, as material behavior models are essentially simplified representations of the actual behavior of footing and soil. Understanding soil deformation behavior is crucial for accurate engineering calculations and designs, making these findings valuable for geotechnical and construction engineering applications. Doi: 10.28991/CEJ-2024-010-07-016 Full Text: PDF